2019
DOI: 10.3847/2041-8213/ab0bb5
|View full text |Cite
|
Sign up to set email alerts
|

On the Anomalous Acceleration of 1I/2017 U1 ‘Oumuamua

Abstract: We show that the P ∼ 8 h photometric period and the astrometrically measured A ng ∼ 2.5 × 10 −4 cm s −2 non-gravitational acceleration (at r ∼ 1.4 AU) of the interstellar object 1I/2017 ('Oumuamua) can be explained by a nozzle-like venting of volatiles whose activity migrated to track the subsolar location on the object's surface. Adopting the assumption that 'Oumuamua was an elongated a × b × c ellipsoid, this model produces a pendulum-like rotation of the body and implies a long semiaxis a ∼ 5A ng P 2 /4π 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 30 publications
1
52
1
Order By: Relevance
“…Our research represents the first attempt to fit 'Oumuamua's light curve using a physical model. (Recently published research by Seligman et al 2019 did use a physical model with torque to explain 'Oumuamua's light curve, but they did not carry out multi-dimensional model fitting, so their results are only suggestive; the computational tasks are completely incomparable: where we had to compute hundreds of millions of physical models, they only computed a few.) The fundamental advantage of such an approach is that torque can be modeled directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research represents the first attempt to fit 'Oumuamua's light curve using a physical model. (Recently published research by Seligman et al 2019 did use a physical model with torque to explain 'Oumuamua's light curve, but they did not carry out multi-dimensional model fitting, so their results are only suggestive; the computational tasks are completely incomparable: where we had to compute hundreds of millions of physical models, they only computed a few.) The fundamental advantage of such an approach is that torque can be modeled directly.…”
Section: Discussionmentioning
confidence: 99%
“…as a triaxial ellipsoid) and albedo variations across the surface, or try different torque prescriptions (e.g. the one used by Seligman et al 2019). Finally, more advanced solar sail models (with some curvature and variable albedo) could be developed, with the hope that they can both explain the observed light curve and have self-consistent torque and linear non-gravitational acceleration (both driven by solar radiation).…”
Section: Discussionmentioning
confidence: 99%
“…As a NASA press release (number 18-056 of 28 June 2018) put it, when 'Oumuamua disappeared from view close to Neptune's orbit, it was 40,000 km further away than if only gravitational force had been acting. NGA was reported as 4.92 ± 0.16 × 10 −6 m/s 2 at a distance of 1 AU from the sun [21]. This radially outward acceleration is about one-thousandth of solar gravitation and was interpreted as resulting from ejection of about 10 kg of mass each second towards the sun at a velocity of 300 m/s [22].…”
Section: Data Obtained From Cosmologists' Observationsmentioning
confidence: 97%
“…'Oumuamua's anomalous acceleration away from the sun became linked to explanations for behavior of comet-like objects. Thus, detailed analysis of its light curve concluded that 'Oumuamua was most likely "a thin disc (slab) experiencing moderate torque from outgassing" [25], and the most authoritative survey of its NGA [21] found "comet-like outgassing to be the most physically plausible explanation". The nature of the outgassing, however, was not agreed upon.…”
Section: Hypotheses In Relation To 'Oumuamuamentioning
confidence: 99%
“…Spectroscopic observations primarily suggested a reddish color, which could be either cometary or asteroidal in origin (Jewitt 2017, Masiero 2017, Ye et al 2017, Bannister et al 2017, Meech et al, 2017Fitzsimmons et al, 2018). While non-gravitational cometary-like acceleration was detected (Micheli et al, 2018;Seligman et al, 2019), no spectroscopic evidence of outgassing was directly found (Ye et al, 2017;Fitzsimmons et al, 2018;Park et al, 2018;Trilling et al, 2018). This could suggest that icy interstellar objects develop a thick, insulating mantle that would inhibit outgassing (Jewitt, 2017;Fitzsimmons et al, 2018).…”
Section: Introductionmentioning
confidence: 99%